THE EFFECT OF SOCIAL SUPPORT ON ELDERLY RESILIENCE:A CASE STUDY IN SUKAMANAH VILLAGE, PANGALENGAN SUB-DISTRICT,BANDUNG REGENCY, WEST JAVA - Dayne Trikora Wardhani (INJOSEDU: International Journal of Social and Education, 2026)
Older adults constitute a population group that experiences various biological, psychological, and social changes as part of the aging process. These changes may affect their ability to maintain well-being and social functioning. One important factor believed to play a role in sustaining the psychosocial resilience of older adults is social support received from family members and the surrounding social environment. This study aims to analyze the effect of social support on the resilience of older adults in Sukamanah Village, Pangalengan Sub-district, Bandung Regency, West Java. This study employed a quantitative approach with descriptive and analytical designs. The respondents consisted of 57 older adults aged 60 years and above, selected using purposive sampling. Data were collected through structured questionnaires measuring social support and elderly resilience. Data analysis was conducted using descriptive statistics, Pearson and Spearman correlation tests, and simple linear regression analysis. The results show that the level of social support among older adults falls within the moderate to high category, with a mean score of 171.77, while the level of elderly resilience is categorized as high, with a mean score of 4.21. Correlation analysis indicates a positive and significant relationship between social support and elderly resilience. Furthermore, the simple linear regression analysis reveals that social support has a significant effect on elderly resilience, contributing 23.6% to the variance in resilience. These findings suggest that older adults who receive better social support tend to have higher adaptive capacity and psychological resilience in facing challenges in later life. This study concludes that social support is an important factor in strengthening elderly resilience. Therefore, strengthening family- and community-based social support should become a key priority in the planning of programs and policies for elderly welfare at the village level